effect of the program of health of the family on the tax of infantile mortality in the pertaining to the state of CearÃ cities - Edilmar Carvalho de Lima (2008)
This dissertation investigates the influence of the Family Health Program (Programa de SaÃde da FamÃlia or PSF in Portuguese) on the Infant Mortality Rate (IMR) and on its main intermediaries determinants in the municipalities of CearÃ (no prenatal care, breastfeeding and desnutrition). As methodology of evaluation it was used multivariate and ecological reduced form models usual to the Health Economics area. The use of reduced form equations allows a greater detail of how each socioeconomic and political factor influence the group of linked events that may lead to the tragic outcome of child mortality. The empirical results show a differential effect for some socio-economic factors and health determinants for the models of prenatal care, breastfeeding, child desnutrition and infant mortality. Regarding the PSF, it was observed its significant influence on the four ecological models of reduced form equations which shows its strength and effectiveness in reducing child mortality, acting in several intermediate stages of the development of the child. In conclusion the public sector can continue intensifying the form of allocation of resources to this primary health care program.